PARAMETRIC STUDY ON STRUCTURAL BEHAVIOUR OF BAMBOO GEODESIC DOME USING RECIPROCAL-TENSION (RECTION) SYSTEM - Irwanuddin, Irfan
Both reciprocal and tensegrity structural system are commonly used in varied architectural projects. Meanwhile, there are some researchers hypothetically stating the possible combination between the two systems. Therefore, several field experiments were conducted in order to challenge those statements. Large geodesic dome structures were built with an aim to establish a new structural system called reciprocal-tension (rection). These processes were done purely by using field construction without a deep understanding of structural consequences. Hence, some errors in construction were unavoidable. A digital simulation in structural engineering using parametric method is emerging with the development of computational tools. This could be an opportunity to solve the problems in rection experiments process, especially related to design and its structural behavior consequences. The aim of this research was to identify the structural behavior of rection dome, specifically with bamboo as its struts material. Three design aspects such as struts diameter, dome span, and geometry became the main parameter being tested in this research. Field experiments and digital simulation were chosen as the methods. The goal of the experimental part was to calibrate the data between the real and simulation, while the digital simulation part worked as the extension study of the main parametric investigation. Based on the study, it was concluded that (1) rection module works differently compared to reciprocal and tensegrity. There is more bending force compared to reciprocal, but with less tension force compared to tensegrity. (2) Increase in struts diameter of the same geometry resulted in the increase of overall stiffness, deformation quality, struts deflection, but accompanied by the increase of total load and its maximum tension force. The result also draws that (3) The increase in span of the same geometry resulted in the decrease of load quality, struts deflection quality, cable tension force quality, deformation quality, and overall stiffness quality, but with an approximately equal construction complexity. In addition to the results, the investigation of membrane load simulation showing that there is a possibility of adding a membrane material as the rection dome envelope as a part of its development purpose.